Complete genome sequence of Vibrio gazogenes PB1: an estuarine bacterium capable of producing prodigiosin from starch or cellulose - Baby, Bincy; Vijay, Dhanya; Philip, Pretty S.; Alnuaimi, Afra A.; Almansoori, Hessa M.; Areidat, Sarah O.; Khan, Gulfaraz; Vijayan, Ranjit; Akhtar, M. Kalim (Frontiers in Marine Science, 2023)
Vibrio is a genus of gram-negative, rod-shaped, motile bacteria commonly found in saltwater. One species in particular, Vibrio gazogenes PB1, sourced from an estuarine environment, is known to produce the secondary metabolite, prodigiosin. This high-value compound has potential uses as an antibiotic, a fungicide, and an anti-cancer agent. To further explore its metabolic and genetic features for biotechnological purposes, the complete genome sequence of V. gazogenes PB1 was determined by Illumina and Pacbio sequencing. Two chromosomes were assembled with a mean coverage of 293x. Chromosome 1 is 3.5 Mbp in size with 45.3% GC content and chromosome 2 is 1.2 Mbp in size with 45.1% GC content. The entire genome harbours 4178 genes, of which 3988 are protein-coding and 114 are RNA-coding. A total of 55 virulence-related genes, 38 antimicrobial resistance genes, 48 transposase sequences, 2 intact prophage regions, and 10 genomic islands were present within the genome. Six genes associated with the degradation of cellulose and starch were also identified within the genome. Four of them were strongly up-regulated, as confirmed by RT-qPCR, thus providing strong evidence for their involvement in starch and cellulose degradation. Quite importantly, we demonstrate for the first time that starch and cellulose is associated with the synthesis of prodigiosin in a native prodigiosin-producing bacterium. The prodigiosin titres obtained in the presence of cellulose were on par with glucose as the carbon source which lends further support in the use of V. gazogenes PB1 as a biotechnological host for prodigiosin production.